Implications of the Covid-19 Pandemic: Canvassing Opinion from Planning Professionals. (2nd January 2022) - Bolleter, Julian; Edwards, Nicole; Cameron, Robert; Duckworth, Anthony; Freestone, Robert; Foster, Sarah; Hooper, Paula
ABSTRACT: By the end of 2020, the COVID-19 pandemic had exceeded 83 million cases worldwide. Given the shared origins of planning and public health, new living and social conditions have prompted an interest in how urban planning could respond to the pandemic's associated implications. In 2020, a national online survey Plan My Australia was conducted among planning experts (n = 161), in part, to identify new challenges facing urban planning and design due to the pandemic. The findings reported here revealed that many experts identified better planning for future pandemics in Australia could require some reconsideration of city size, urban density, self-sufficiency, public transport use, open space provision and housing design.